Identifying the factors promoting colorectal cancer screening uptake in Hong Kong using Andersen’s behavioural model of health services use - Dorothy N. S. Chan; K. C. Choi; Doreen W. H. Au; Winnie K. W. So (BMC Public Health, 2022)
Abstract Background Colorectal cancer (CRC) screening is an effective strategy to aid early cancer detection. However, the decision to undergo screening can be affected by a variety of factors. The aims of this study were to examine current CRC screening uptake in Hong Kong and identify the factors associated with it using Andersen’s Behavioural Model as a guiding framework. Methods This cross-sectional study was conducted in Hong Kong from August 2019 to December 2020. A sample of 1317 Chinese individuals aged 50 to 75 years were recruited and completed a survey to identify predisposing, enabling, and need-for-care factors, and the colorectal cancer screening uptake rate (faecal occult blood test [FOBT] or faecal immunochemical test [FIT] and colonoscopy) was determined. Results The FOBT/FIT uptake rate was 43.9%, while that of the colonoscopy was 26.0%. The provision of a government subsidy for screening and the provision of information booklets were the most significant and second most significant enabling factors for FOBT/FIT uptake, respectively. Visiting a doctor five times or more in the previous year and being recommended to undergo a CRC screening by a doctor, were the most significant enabling factors for colonoscopy uptake. Age, the perceived benefit of and barriers to screening were important predisposing factors for FOBT/FIT and colonoscopy uptake. Conclusions Screening uptake rates in Hong Kong have significantly increased over the last decade, although they remain lower than those in other countries. Continual efforts are warranted to promote government-subsidised screening. Relevant educational materials that address the barriers identified in this study should be developed and disseminated to the public.